Selection gain and interrelations between agronomic traits in wheat F5 genotypes - Meier, Carine; Meira, Daniela; Marchioro, Volmir Sergio; Olivoto, Tiago; Klein, Luís Antônio; Queiroz de Souza, Velci (Revista Ceres, 2025)
This work aimed to estimate the variance components and genetic parameters, the selection gain, and the cause and effect relationships among traits in order to identify important traits for direct and indirect selection of wheat (Triticum aestivum L.) lines. Three strategies were used to obtain selection gains: direct and indirect selection, an index based on “ranks,” and the Smith and Hazel index. In the 2017 crop season in Brazil, 420 wheat lines from the F5 generation were conducted in families with intercalary controls. High heritability of spike weight, number of kernels, and total kernel weight resulted in the best direct selection gains. The selection of plants with a high number of tillers resulted in grain yield improvement. The use of selection indexes is important in advanced wheat lines; they promote genetic gains distributed among agronomic traits.